1997
DOI: 10.3758/bf03211311
|View full text |Cite
|
Sign up to set email alerts
|

Age differences in the allocation of study time account for age differences in memory performance

Abstract: How aging affects the utilization of monitoring in the allocation of study time was investigated by having adults learn paired associates during multiple study-test trials. During each trial, a subject paced the presentation of individual items and later judged the likelihood of recalling each item on the upcoming test; after all items had been studied and judged, recall occurred. For both age groups in Study 1, (1) people's judgments were highly accurate at predicting recall and (2) intraindividual correlatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
144
2
5

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(168 citation statements)
references
References 35 publications
(27 reference statements)
17
144
2
5
Order By: Relevance
“…This pattern replicates previously reported results (e.g., Dunlosky & Connor, 1997;Mazzoni et al, 1990;Nelson & Leonesio, 1988;Zacks, 1969) and is consistent with the view of study time as a strategic tool that is used to regulate memory performance. 4 Figure 1 (top panel) presents mean recall for easy and difficult items for the self-paced and fixed-rate conditions.…”
Section: Resultssupporting
confidence: 92%
“…This pattern replicates previously reported results (e.g., Dunlosky & Connor, 1997;Mazzoni et al, 1990;Nelson & Leonesio, 1988;Zacks, 1969) and is consistent with the view of study time as a strategic tool that is used to regulate memory performance. 4 Figure 1 (top panel) presents mean recall for easy and difficult items for the self-paced and fixed-rate conditions.…”
Section: Resultssupporting
confidence: 92%
“…Alternatively, immediate JOLs, which do not involve a diagnostic retrieval attempt, do have reason to rely on MPT. In support of the MPT heuristic, have noted that when judgments are delayed, the UWP effect is either reversed (Dunlosky & Connor, 1997;Koriat & Ma'ayan, 2005, Koriat, Ma'ayan, Sheffer & Bjork, 2006, absent Meeter & Nelson, 2003), or extremely truncated (Serra & Dunlosky, 2005). Furthermore, showed that past test performance predicted immediate JOLs, but not delayed JOLs.…”
mentioning
confidence: 85%
“…The subsequent research examining study-time allocation converges on the conclu-sion that people tend to allocate their study time to items they judge to be difficult (Cull & Zechmeister, 1994;Dunlosky & Connor, 1997;Dunlosky & Hertzog, 1997;Kellas & Butterfield, 1971;Le Ny, Denhiere, & Le Taillanter, 1972;Mazzoni & Cornoldi, 1993;Mazzoni, Cornoldi, & Marchitelli, 1990;Mazzoni, Cornoldi, Tomat, & Vecchi, 1997;Nelson, Dunlosky, Graf, & Narens, 1994;Nelson & Leonesio, 1988;Thiede & Dunlosky, 1999). The present experiment investigated whether participants would allocate more study time to items judged to be more difficult in both congruent and incongruent task-test processing conditions.…”
Section: Methodsmentioning
confidence: 99%